2012
DOI: 10.1007/s11250-012-0194-1
|View full text |Cite
|
Sign up to set email alerts
|

Traditional breeding objectives and practices of goat, sheep and cattle smallholders in The Gambia and implications in relation to the design of breeding interventions

Abstract: This paper describes the traditional breeding objectives and practices of West African Dwarf goat, Djallonke sheep, and N'dama cattle keepers in The Gambia and discusses the implications of these on the design of breeding-related interventions to improve livestock productivity. Data were collected via surveys implemented within three study sites in The Gambia, where traditional mixed crop-livestock smallholder farming predominates. The surveys comprised a participatory rural appraisal conducted in nine communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…The second relates to the role of livestock to the livelihood of their keeper, which can be diverse (see Table 3) and also varies by system. In 'agro-pastoral and pastoral' and 'extensive mixed crop-livestock' systems, livelihood risk mitigation is of high importance, and the keeping of particular livestock species for savings and insurance purposes can be as, or more, important than the keep-ing of that species as a productive asset (see, for example, Ejlersten et al 2012). To this end, the more adapted, indigenous breed types are superior.…”
Section: Use Of Breed Types In Developing Country Livestock Productiomentioning
confidence: 99%
“…The second relates to the role of livestock to the livelihood of their keeper, which can be diverse (see Table 3) and also varies by system. In 'agro-pastoral and pastoral' and 'extensive mixed crop-livestock' systems, livelihood risk mitigation is of high importance, and the keeping of particular livestock species for savings and insurance purposes can be as, or more, important than the keep-ing of that species as a productive asset (see, for example, Ejlersten et al 2012). To this end, the more adapted, indigenous breed types are superior.…”
Section: Use Of Breed Types In Developing Country Livestock Productiomentioning
confidence: 99%
“…For smallholder farmers in mixed crop–livestock production systems, securing a supply of manure can be among the most important reasons for keeping animals. For example, a study conducted by [27] in the Gambia, indicated that among mixed farmers with fewer than ten cattle, manure supply ranked as the second most important reason for keeping cows and third for keeping bulls. Among farmers with larger herds, manure supply was reported to be the most important livestock function.…”
Section: Introductionmentioning
confidence: 99%
“…Jabbar and Diedhiou (2003) examined breed preferences in Nigeria based on the rating of breed traits and market data using hedonic pricing. Ejlertsen et al (2013) and Benison et al (1997) assessed the production objectives and selection criteria of livestock owners in The Gambia, also using a rating matrix. Few studies have taken into account the heterogeneity of farmers and the factors that influence their production objectives and trait preferences for cattle (Benison et al, 1997;Tano et al, 2003;Ouma et al, 2007;Ndumu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%